2007
DOI: 10.1161/01.res.0000260171.52224.6b
|View full text |Cite
|
Sign up to set email alerts
|

Deoxymyoglobin Is a Nitrite Reductase That Generates Nitric Oxide and Regulates Mitochondrial Respiration

Abstract: Abstract-Previous studies have revealed a novel interaction between deoxyhemoglobin and nitrite to generate nitric oxide (NO) in blood. It has been proposed that nitrite acts as an endocrine reservoir of NO and contributes to hypoxic vasodilation and signaling. Here, we characterize the nitrite reductase activity of deoxymyoglobin, which reduces nitrite approximately 36 times faster than deoxyhemoglobin because of its lower heme redox potential. We hypothesize that physiologically this reaction releases NO in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

29
573
1
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 529 publications
(605 citation statements)
references
References 43 publications
29
573
1
2
Order By: Relevance
“…Whereas XOR has been proposed as being responsible for the conversion of nitrite to NO • in the heart by Webb et al (11), Zweier et al (19), and recently Baker et al (20), no such effect was observed by our groups (14,15). We have recently demonstrated that a decrease in myocardial oxygen tension drives the conversion of oxymyoglobin to deoxyMb, which reacts with nitrite to generate NO • , regulating cardiac energetics and function (14,15). Whether deoxyMb or XOR is responsible for nitrite reduction to NO • in the ischemic heart to mediate cytoprotection remains unclear.…”
contrasting
confidence: 49%
See 3 more Smart Citations
“…Whereas XOR has been proposed as being responsible for the conversion of nitrite to NO • in the heart by Webb et al (11), Zweier et al (19), and recently Baker et al (20), no such effect was observed by our groups (14,15). We have recently demonstrated that a decrease in myocardial oxygen tension drives the conversion of oxymyoglobin to deoxyMb, which reacts with nitrite to generate NO • , regulating cardiac energetics and function (14,15). Whether deoxyMb or XOR is responsible for nitrite reduction to NO • in the ischemic heart to mediate cytoprotection remains unclear.…”
contrasting
confidence: 49%
“…The exact mechanisms behind the cytoprotective effects of exogenous nitrite, however, are still a matter of debate. Whereas XOR has been proposed as being responsible for the conversion of nitrite to NO • in the heart by Webb et al (11), Zweier et al (19), and recently Baker et al (20), no such effect was observed by our groups (14,15). We have recently demonstrated that a decrease in myocardial oxygen tension drives the conversion of oxymyoglobin to deoxyMb, which reacts with nitrite to generate NO • , regulating cardiac energetics and function (14,15).…”
mentioning
confidence: 60%
See 2 more Smart Citations
“…good or bad NO, the complex interplay between NO and mitochondria remains to be defined in the context of fatty liver disease from alcohol and obesity. Moreover, the critical importance of understanding the regulation of the mitochondrial respiratory chain by NO in hepatic physiology and pathophysiology is supported by several studies demonstrating that localized NO production can occur within the organelle through a specific mitochondrial NOS isoform or via metabolism of nitrite to NO [119][120][121].…”
Section: Interplay Between Nitric Oxide and Mitochondria In Fatty LIVmentioning
confidence: 99%